Genetic association testing using the GENESIS R/Bioconductor package - Gogarten, Stephanie M; Sofer, Tamar; Chen, Han; Yu, Chaoyu; Brody, Jennifer A; Thornton, Timothy A; Rice, Kenneth M; Conomos, Matthew P (Bioinformatics (Oxford, England), 2019)
The Genomic Data Storage (GDS) format provides efficient storage and retrieval of genotypes measured by microarrays and sequencing. We developed GENESIS to perform various single- and aggregate-variant association tests using genotype data stored in GDS format. GENESIS implements highly flexible mixed models, allowing for different link functions, multiple variance components and phenotypic heteroskedasticity. GENESIS integrates cohesively with other R/Bioconductor packages to build a complete genomic analysis workflow entirely within the R environment. https://bioconductor.org/packages/GENESIS; vignettes included. Supplementary data are available at Bioinformatics online.